On the effect of water content on fatigue mechanical behaviors of mud-shale under stress disturbance conditions - Li, Xuguang; Wu, Jihuan; Yang, Haonan; Wang, Yu (Frontiers in Materials, 2023)
This paper aims to reveal the fatigue damage and instability behaviors of mud-shale under multistage increasing-amplitude fatigue loading. The fatigue loading tests combined with real-time acoustic emission (AE) monitoring technique were employed to investigate the influence of water content on the deformation, damage, and fracture characteristics. Testing results show that rock fatigue life decreases with the increase of water content, and the hysteresis curve changes regularly with time. The failure process can be divided into three stages: initial stage, stable development stage and acceleration stage. The acoustic emission output activities were also influenced by the water content. The acoustic emission ring count and acoustic emission energy both decrease with increasing water ratio and the accumulative count and energy are the least for a sample having high water ratio. The acoustic emission activity shows a sudden increase trend at the amplitude-increasing moment, indicating the occurrence of strong damage within rock sample. The damage propagation within a cyclic loading stage is relatively small compared to the stress-increasing moment. The results are helpful to understand the fatigue mechanical responses of water-sensitive soft rock, as well as the slope stability of the open-pit mine. The research results have important theoretical and practical significance for promoting slope treatment and disaster prevention.